2014
DOI: 10.15252/embj.201488289
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cargo‐selective endocytosis by dynamin 2 GTPase‐activating protein girdin

Abstract: In clathrin-mediated endocytosis (CME), specificity and selectivity for cargoes are thought to be tightly regulated by cargo-specific adaptors for distinct cellular functions. Here, we show that the actin-binding protein girdin is a regulator of cargo-selective CME. Girdin interacts with dynamin 2, a GTPase that excises endocytic vesicles from the plasma membrane, and functions as its GTPase-activating protein. Interestingly, girdin depletion leads to the defect in clathrin-coated pit formation in the center o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…We recently reported that Girdin functioned as a GAP for dynamin 2 and regulated clathrin dependent endocytosis in a cargo specific manner [18]. The study revealed that Girdin regulated the endocytosis of E-cadherin in MDCK cells where R-Ras was not expressed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We recently reported that Girdin functioned as a GAP for dynamin 2 and regulated clathrin dependent endocytosis in a cargo specific manner [18]. The study revealed that Girdin regulated the endocytosis of E-cadherin in MDCK cells where R-Ras was not expressed.…”
Section: Discussionmentioning
confidence: 97%
“…However, the function of Girdin in those mature endothelial cells has not been addressed. An insight into the involvement of Girdin in the transendothelial permeability has come from our previous studies that showed that Girdin functions as a GAP for dynamine 2 and regulates the endocytosis of E-cadherin and transferrin receptor in MDCK cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies identified that the CT domain interacts with Par-3 as well as actin filaments, whereas the NT domain interacts with DISC1 and dynamin (Fig. 1A) [1,3,11,12]. To identify which domains of Girdin are responsible for its interaction with kinesin-1, we constructed fragments of Girdin and transfected them with KIF5A, a representative isoform of kinesin-1 ( Fig.…”
Section: Mapping Girdin and Kinesin-1 Interacting Domainsmentioning
confidence: 99%
“…We and others have identified several Girdin-interacting proteins, which include the Ga proteins [9,10], dynamin [11], partitioning-defective gene 3 (Par-3), which is a regulator of cell polarization [12], and Disrupted-In-Schizophrenia 1 (DISC1), which is a neuronal scaffold protein whose dysfunction is responsible for development of major mental disorders [3]. However, the mechanisms of Girdin-regulated cell migration have not yet been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…11 The function of Gipie is distinct from that of Girdin because of the low homology between the functional C-terminal domains of the proteins, with Girdin known to regulate cellular motility and endocytosis. 12,13 We found that Gipie localizes at the ER and Golgi apparatus, and it forms a complex with GRP78 and IRE1α through its C-terminal domain in endothelial cells, where it stabilizes the interaction between GRP78 and IRE1α, reducing the c-Jun N-terminal kinase (JNK) activation and cell death induced by chemical ER stress. However, the roles of Gipie in VSMCs and vascular disease models have been not investigated to date.…”
mentioning
confidence: 99%